2006
DOI: 10.1088/0268-1242/21/7/019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Pt barrier on Ti/Al/Pt/Au ohmic contacts to n-GaN studied by Rutherford backscattering spectrometry and x-ray diffraction

Abstract: The diffusion barrier effect of Pt has been investigated in Ti/Al/Pt/Au ohmic contacts to n-GaN. Severe indiffusion, outdiffusion of Pt and outdiffusion of Ga have been found in 450 • C annealed samples according to the Rutherford backscattering spectrometry (RBS) results. At the same time, the reaction between Ga and Pt has also been identified by glancing angle synchrotron irradiation x-ray diffraction (GASIXRD) in the samples annealed at 450 • C. A higher annealing temperature causes Pt to indiffuse into Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…This is considered to be due to that most of the Ni atoms in the Au-Ni solid solution began to be driven out when the sample was annealed at higher temperatures. On the other hand, Hu et al [10] reported that the peak of Au(1 1 1) shifted all the way to an angle higher than 0.25°as the annealing temperature was increased above 450°C, which finding had been explained elsewhere by the formation of Au-Ga solution [13]. However, in this experiment, the peak of Au(1 1 1) did not shift further as the annealing temperature was increased above 500°C.…”
Section: Methodscontrasting
confidence: 55%
See 2 more Smart Citations
“…This is considered to be due to that most of the Ni atoms in the Au-Ni solid solution began to be driven out when the sample was annealed at higher temperatures. On the other hand, Hu et al [10] reported that the peak of Au(1 1 1) shifted all the way to an angle higher than 0.25°as the annealing temperature was increased above 450°C, which finding had been explained elsewhere by the formation of Au-Ga solution [13]. However, in this experiment, the peak of Au(1 1 1) did not shift further as the annealing temperature was increased above 500°C.…”
Section: Methodscontrasting
confidence: 55%
“…Accordingly, Au and Ni metals were deposited along the <1 1 1> direction, the preferred growth orientation on a (0 0 0 1) plane of GaN polycrystal. These results show that the epitaxial microstructures of Au and Ni were formed on the poly-GaN film [10,19]. Hence, the orientation relationships for Au/poly-GaN and Ni/poly-GaN are Au(1 1 1)//polyGaN(0 0 0 2) and Ni(1 1 1)//poly-GaN(0 0 0 2), respectively.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, platinum (Pt) is one of the most important transition metal, being used extensively in semiconductor devices including an electrode material for the capacitor structures in memory devices [5]. Additionally, Pt-based metallization schemes have been employed to obtain reliable ohmic contacts to p-GaN [6] and n-GaN [7]. Furthermore, since hydrogen atoms can diffuse very quickly towards Pt-GaN interface, the combination of GaN with catalytic Pt has been used to realize sensors for hydrogen and hydrocarbon gases [8].…”
Section: Introductionmentioning
confidence: 99%